Efficiency and outcome of non-invasive versus invasive positive pressure ventilation therapy in respiratory failure due to chronic obstructive pulmonary disease - Valiollah Amri-Maleh; Mahmood Monadi; Behzad Hidari; Parviz Amri-Maleh; Ali Bijani (Babol University of Medical Sciences, 2016)
Background: Application noninvasive ventilation in the patients with exacerbation of chronic obstructive pulmonary disease (COPD) reduced mortality. This case-control study was designed to compare efficiency and outcome of non-invasive (NIV) versus invasive positive pressure ventilation (IPPV) in respiratory failure due to COPD Methods: The patients were assigned to NIV or IPPV intermittantly.The clinical parameters, including RR (respiratory rate), BP (blood pressure), HR (heart rate) and PH, PaCO2, PaO2 before and 1, 4 and 24 h after treatment were measured. Demographic information such as age, sex, severity of disease based on APACHE score, length of stay and outcome were recorded Results: Fifty patients were enrolled in the NIV group and 50 patients in IPPV. The mean age was 70.5 in NIV and 63.9 in invasive ventilation group (p>0.05). In IPPV group, the average values of PH: PCO2: and PO2, were 7.22±0.11, 69.64 + 24.25: and 68.86±24.41 .In NIV, the respective values were 7.30±0.07, 83.94±18.95, and 60.60±19.88.  In NIV group, after 1, 4 and 24 h treatment, the clinical and ventilation parameters were stable. The mean APACHE score in was IPPV, 26.46±5.45 and in NIV was 12.26±5.54 (p<0.05). The average length of hospital stay in IPPV was 15.90±10 and in NIV 8.12±6.49 days (p<0.05). The total mortality in the NIV was 4 (8%) and in IPPV, 27 patients (54%) (p<0.05). Conclusion: This study indicates that using NIPPV is a useful therapeutic mode of treatment for respiratory failure with acceptable success rate and lower mortality. The application of NIPPV reduces hospital stay, intubation and its consequent complications